PENGEMBANGAN UMKM BONTOT MELALUI INOVASI PRODUK DI DESA DOMAS SERANG BANTEN - Remvilina Sari; Siti Nurjanah; Ahmad Ramdani; Ende Ende (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The Student Work Lecture Program is one of Bina Bangsa university programs as one of Tri Dharma Higher Education implementations, namely student service to the community to help and guide the community in utilizing resources that are expected to help develop the potential of the community. This program aligns research and community service activities from lecturers and students across science and brings togetherness values. This implementation is an effort to develop Micro, Small and Medium Enterprises for small products to increase competitiveness as a regional specialty food product that is in demand by consumers through product innovation improvements—solving problems on product innovation of bontot with packaging that has been vacuumed so that it can last a long time to be marketed outside the region and product innovation of bontot crackers through flavour variants, size variants and supported by more attractive and competitive packaging. The approach method used is socialization, training and mentoring. This activity is carried out to increase product innovation so that the selling value of bontot products increases. It is collecting data obtained from the exploration of information from various sources